2014
DOI: 10.1002/mop.28420
|View full text |Cite
|
Sign up to set email alerts
|

Development of passive millimeter wave imaging for concealed weapon detection indoors

Abstract: this MZI waveguide sensor with optimized sensing length of 1,1515 mm is 225.4 dB/RIU. We know that DL 53r=sensitivity , where 3r is the standard deviation of the system [12]. Following the magnification of the measured standard deviation 3r in Figure 4(b), the refractive sensing DL in three standard deviations is with the magnitude of 10 26 RIU. CONCLUSIONThis study theoretically and experimentally investigated the periodic ambiguity of the MZI waveguide sensor without increasing complexity in standard fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…When the value of d increases to 712 mm, c a falls to 0.896. It shall be noted that the spillover loss has been included in formula (4).…”
Section: Quasi-optics Design and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When the value of d increases to 712 mm, c a falls to 0.896. It shall be noted that the spillover loss has been included in formula (4).…”
Section: Quasi-optics Design and Analysismentioning
confidence: 99%
“…This makes MMW technology favorable for security surveillance, especially for the detection of weapons concealed under peoples' clothes [1][2][3][4]. Focal plane array (FPA) technology is useful for MMW imaging system due to its ability of greatly increasing the imaging frame rate [5].…”
Section: Introductionmentioning
confidence: 99%
“…One of the important applications of PMMW imaging is doubtlessly the detection of hidden weapons in airports and other checkpoint sites . For the recent years, many researchers have demonstrated that PMMW imaging can be an effective method for detecting and imaging concealed dangerous objects such as guns, knives, dielectric explosives with fair image features . Although active imaging systems at millimeter wave frequencies have the potential of being harmful to the nearby people, PMMW imaging technology provides completely safe detection of concealed weapons because of the fact that PMMW receiver only gathers the passive, non‐ionizing radiation from the target.…”
Section: Introductionmentioning
confidence: 99%
“…Various imaging techniques include infrared imaging [5,6], passive millimeter-wave (MMW) imaging [7][8][9], active MMW imaging [10,11], X-ray imaging [12,13] and holographic imaging [14][15][16][17] have been investigated for concealed metallic object detection. Recent studies have demonstrated that passive MMW imaging has the most potential to become a useful tool to identify concealed MFOs under clothing [18,19], which has been investigated for various applications include security, military, surveillance and biomedical [20].…”
Section: Introductionmentioning
confidence: 99%